The Effect of Peer Conference Strategy and Self-Confidence toward the Writing Skill of Recount Text (An Experimental Research on the Grade Eight Students of SMPN 22 Padang) - Gusti Melia; M Zaim; Hamzah Hamzah (Jurnal Aplikasi IPTEK Indonesia, 2019)
Writing is one of the important skills that should be mastered by the students. In writing, the students need to express their feeling in a good way and well-organized. In fact, most of students were lack of idea and could not write well-organized in written form. The purpose of this research was to find out the effect of Peer Conference Strategy and students’ self-confidence toward the writing skill of recount text. The sample consists of 64 students. The research data was collected using writing test and self-confidence questionnaires. Data analysis was using t-test and Two Ways ANOVA. The analysis of the research results shows that (1) Peer Conference strategy was effective than expository strategy; (2) Peer Conference strategy was effective to high self-confidence students; (3) Peer Conference strategy was not effective to low self-confidence students; (4) There was an interaction both teaching strategies and self-confidence in writing skill.